Transpedicular Stabilization Complications in Thoracic Region of the Spine After SCI - Three Cases Report and Literature Review - Łukowicz, Małgorzata; Mackiewicz-Milewska, Magdalena; Lach-Inszczak, Sabina; Szymkuć, Iwona; Hagner, Wojciech (Medical and Biological Sciences, 2012)
A case report of three cases of complications after transpedicular stabilization in thoracic part of the spine. Objectives. The aim of the study was to report the complications after surgical stabilization in thoracic level of the spine that could be very dangerous and cause many symptoms. All patients were treated in The Department of Rehabilitation, University Hospital in Bydgoszcz, Collegium Medicum of Nicolaus Copernicus University in Bydgoszcz, Poland Case report 1. The case of 24 year old patient after spinal fracture within T9 as well as T12 level was introduced. The patient was subjected to transpedicular stabilization within the levels of T8-T10 and T11-L2. In ASIA classification A, the lack of any sensation in sacral segments, no anal sphincter motor activity was noticed. Complications manifested by dislocation of screws as well as postoperative wound infection occurred, what caused the necessity for the stabilizer removal. These complications exerted harmful effect on early rehabilitation process. The patient underwent three surgical procedures resulted from dislocation of screws. Case report 2. 31 year old male patient after SCI in T6 region of the spine. He was treated with transpedicular stabilization within the levels of T5-T6. The complication was screw translocation in vertebral body T5 and connecting aortic aneurysm. He was successfully operated by thoracic surgeons. Case report 3. 26 year old male patient after fracture of T5 and T6 vertebra column. He was operated with transpedicular stabilization. He had fever and respiratory tract infection symptoms; after radiological examination the diagnosis of pleuritis was stated and a dislocation of screw in T3 and T4 vertebral body. He was treated conventionally without operation. Conclusions Complications prolong as well as disturb rehabilitation treatment. The control radiographic examinations need to be performed directly after operative treatment to evaluate the stabilization system during walking and assuming the erect position. Increased pain ailments within spinal cord segment that was subjected to surgical procedure may signify the possible dislocation of screws. Such dislocation, noticed within thoracic region, can be life-threatening, because of the nearness of the significant anatomical structures.